Pregnancy Outcomes of Frozen-Thawed Blastocysts versus Blastocysts Derived from Frozen-Thawed Cleavage Embryos: A Retrospective Study - Huy Phuong Tran; Tuyet Thi-Diem Hoang; Ha Le-Bao Tran; Trang Nguyen-Khanh Huynh; Vy Nguyen-Thao Do; Chau Kim Mai; Son Truong Dang (International Journal of Fertility and Sterility)
Background: Limited data exist regarding the outcomes of frozen-thawed cleavage-stage embryos that undergo extended culture to reach the blastocyst stage. This study aimed to compare the pregnancy outcomes between two approaches: transferring blastocysts derived from frozen-thawed cleavage embryos (D3-5 group) and frozen-thawed blastocysts (D5 group).Materials and Methods: This retrospective observational cohort analysis was conducted at Hung Vuong Hospital (CS/HV/24/23) from January 2022 to December 2023. The D3-5 group comprised 167 patients who underwent embryo transfer with frozen-thawed cleavage embryos, which were subsequently cultured for 2 days before being transferred as blastocysts. The D5 group included 342 patients who received frozen-thawed blastocysts. Positive human chorionic gonadotropin (hCG) rate, clinical pregnancy rate, ongoing pregnancy rate, live birth rate, pregnancy failure rate and cancellation rate were compared between the two groups.Results: In the D3-5 group, a significant proportion of cycles (65.3%) were cancelled, primarily due to the absence of developed blastocysts for transfer (85.3%), while the remaining 14.7% of cancellations were attributed to other reasons. Patients in the D3-5 group demonstrated comparable pregnancy outcomes to those in the D5 group: positive hCG rate (52 vs. 53%, P=0.898), clinical pregnancy rate (45 vs. 48%, P=0.785), ongoing pregnancy rate (34 vs. 33%, P=0.873), live birth rate (31 vs. 29%, P=0.839), and pregnancy failure rate (21 vs. 24%, P=0.656).Conclusion: The strategy of culturing frozen-thawed cleavage embryos for two days and transferring them as blastocysts is not inferior to the transfer of frozen-thawed blastocysts. It increases workload for embryologists and poses a risk of cycle cancellation. We propose that the use of frozen-thawed blastocysts may be a more efficient and patient-friendly option.